Educação estética e fotografia na formação de professores em nível do ensino médio: a relevância das contribuições de Adorno e Freire - Oliveira, Moysés Romero Borges (2011)
This paper presents a study about the possibility of an aesthetical education from the project “To take a School through photographical eyes, an educational process that regards photography as an initiate of the Formative Experience. It was elected as a problem: The meaning and the significance of photography produced by the students who are in the teacher’s formation process – high school. A guiding question has been established: Is it possible through the camera lens to initiate the formative experience? Our hypothesis is linked to the perception that aesthetic is a Formative Experience in the emancipation and autonomy process of the individual. The big challenge in the Adorno’s work is Education and Art as a way that breaks with the alienation, as consequence from the cultural industry, in Freire the aesthetic is a form of justice among men. The adopted theoretical framework, in Freire and Adorno, is related to the presence of art aiming the individual’s educational freedom, humanization, autonomy and emancipation. The research’s aims are 1) to understand the formative experience through images in the pictures and through words in the text; 2) to comprehend the influence of the mass imposed by the cultural industry in the students’ formation and 3) to analyze the reference of the student’s trajectory. The documental analysis is the procedure adopted for data collection. Theoretically speaking, the research is based on the hermeneutic approach, bearing on mind Gadamer’s perspective, to analyze and to interpret the collected data. The analyzed material, which means the photographs and autobiographical reports, this study treated as documents produced by students from the teaching method in high school. In this sense, the photograph is taken - in this study – at two levels: as a research method and as the language in the teachers’ education process. The results present photograph as the construction of the formative history of students, a transforming element of the teacher’s gaze, as recognition of their identity and appreciation of their choices, such as resistance to the aesthetic of cultural industry and recreation of autonomy and emancipation as a result of the narrative of their history